Critical thinking : a students introduction - Bassham, Gregory, 1959- (McGraw Hill, 2022)
"The first edition of Critical Thinking: A Student's Introduction grew out of our conviction that a critical thinking text that works-that produces real, measurable improvement in students' critical reasoning skills-must have two essential features: It must be a text that today's gadget-loving students actually read. It must provide abundant, class-tested exercises that give students the practice they need to develop as maturing critical thinkers. In revising Critical Thinking: A Student's Introduction for this edition, we've tried to remain faithful to this original vision. Many passages have been rewritten to make the book clearer and (we hope) more engaging and accessible. In addition, many new readings have been added to keep the text timely and fresh"--
Includes index.
Ages 18+
Grades 10-12
Keywords: Critical thinking -- Textbooks